Diabetes in pregnancy and risk for mother and newborn - Mladenovska Stojkoska, Ivana; Adamova, Katerina; Shubeska Stratrova, Slavica; Jovanovska Mishevska, Sasha; Bitoska, Iskra; Todorova, Biljana; Zivkovic, Marija; Mihajlovska, Djulijana; Toshevska, Marija (My University, 2018)
Introduction: DM in pregnancy carries a risk for the course of pregnancy, mother and fetus. It may be progestational (DM1 and DM2) and gestational DM (GDM). Aim: Bad glycemic control before and after conception increases risk for neonatal mortality and congenital malformations. Material and methods: At the clinic for endocrinology for a period of one year were analyzed the risk factors for GDM, glycemic control, maternal and fetal risks in 43 DM pregnant patients. Results: The patients were aged 25-47 years, one of them (2.4%) with DM1, 5 (11.6%) with DM 2 and 37 (86%) with GDM. Of the risk factors for GDM: 31 (72%) had> 30 years, 2 (4.6%) had GDM in the previous pregnancy (PP), 6 (13.9%) had a dead fetus in PP, 26 (60%) have DM in a family. Average HbA1C was 6,4 %, from which 55,6% had HbA1C>6% and 44,4% had HbA1C<6 %. Hypertension had 10 (23.3%) patients, of whom 7 (16.3%) had hypertension in PP and 3 (7%) in this pregnancy. Pregnancy complications: 3(6.9%) had pre-eclampsia, 12 (27.9%) gave birth before 37 weeks of gestation, of which 4 (9.3%) were over 30 years old and 1 (2.3%) became pregnant with invitro fertilization. From obstetric complications: 11 (25.6%) had polyhydramnios, 4(9.3%) macrosomia. The average body weight of a newborn was 3160 grams. A newborn born with a ventricular septal defect and one with a multiorgan disease. Average APGAR score 7/8. Conclusion: Optimal pre-conception glycemic control with HbA1C<6.5% and in pregnancy HbA1C<6% is required to reduce the risk of spontaneous abortions and congenital anomalies.